Influence of Corporate Governance Mechanisms on Financial Risk and Financial Performance: Evidence from Refinitiv ESG Database - Saif Al Mutairi A.M.; Bakar S.B. (World Scientific and Engineering Academy and Society, 2024)
The present study investigates the relationship between corporate governance (CG) mechanisms and the financial risk and performance of the companies enlisted in the Refinitiv ESG Database. The study drew on the agency theory of CG. It evaluated the effect of board diversity (BD), board independence (BI), CEO duality (CEOD), and gender diversity (GD) on financial risk (FR), comprising of credit (CR) and liquidity risk (LR) and financial performance (FP) measured by returns on asset (ROA) while controlling for firm size, age, and tangible assets. Data is obtained from 2009 to 2019 for panel data regression analysis. The study utilized the Hausman test for model specification. The findings specify that the size of the board positively and significantly impacts FR and FP. Gender diversity negatively and significantly affects credit risk and FP. Board independence positively and significantly influenced FP. The study provides significant implications for scholars and practitioners. 2023, World Scientific and Engineering Academy and Society. All rights reserved.